2018
DOI: 10.1371/journal.pone.0197749
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cognitive load and social anxiety in an emotional anti-saccade task

Abstract: The anti-saccade task has been used to measure attentional control related to general anxiety but less so with social anxiety specifically. Previous research has not been conclusive in suggesting that social anxiety may lead to difficulties in inhibiting faces. It is possible that static face paradigms do not convey a sufficient social threat to elicit an inhibitory response in socially anxious individuals. The aim of the current study was twofold. We investigated the effect of social anxiety on performance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…Although many studies have explored how the WM load affects selective attention in SA individuals, they have yielded inconsistent results. For example, some studies have shown that increased WM load would lead to decreased attention control and greater difficulty for SA individuals or trait anxiety in escaping threat‐related distractors (Berggren et al, 2012 ; McKendrick et al, 2018 ). Interestingly, another study found that high (compared to low) SA individuals were more likely to be distracted by task‐irrelevant face stimuli (e.g., angry faces) and required longer reaction times to recognize target letters in visual search tasks under high cognitive load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have explored how the WM load affects selective attention in SA individuals, they have yielded inconsistent results. For example, some studies have shown that increased WM load would lead to decreased attention control and greater difficulty for SA individuals or trait anxiety in escaping threat‐related distractors (Berggren et al, 2012 ; McKendrick et al, 2018 ). Interestingly, another study found that high (compared to low) SA individuals were more likely to be distracted by task‐irrelevant face stimuli (e.g., angry faces) and required longer reaction times to recognize target letters in visual search tasks under high cognitive load.…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistent results in previous studies may be due to the fact that the WM load was not adequately manipulated. For example, McKendrick et al ( 2018 ) informed participants about the speech task information (e.g., the participants were told that they would have to give a speech to the audience) before completing the anti‐saccade task to increase social‐cognitive load. However, the speech task increases the SA rather than the demands on WM, which is usually regarded as the process of maintaining and manipulating information in a short time (Baddeley, 1992 ).…”
Section: Introductionmentioning
confidence: 99%